Between the aesthetics of picturesque and the documentary uses: the images of popular types and customs in Chile and Peru’s 19th century visual culture (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
Images of popular types and customs were set up as fundamental repertoires in the structure of nation imaginaries in Latin America, hence the importance of its study in order to understand nineteenth-century visual culture in territories such as Chile and Peru. These representations were mainly developed from manual media, in which are discussed matters of taste, associated to an aesthetic of the picturesque; this shows the tensions and convergences of various functions and demands of the model image. However, during the second half of the nineteenth century, this tradition will confront the emergence of the photographic medium. The repercussions and transformations which this implied will be discuss in the present article, considering both the documentary and the informative component that photography would have boost into a repertoire which was mostly constituted, though not exclusively, by an aesthetic of the picturesque. In this way, this paper proposes a historiographic reading that analyses the setting-up of this tradition through particular cases refer to the Chilean and Peruvian context, to think afterwards its reformulation following the incursion of the technical device.
Keywords: Images of types and customs; picturesque aesthetics; voyage of discovery; traditional visual media; early documentary photography